THE EFFICIENCY OF USING DIFFERENT TYPE OF FILTER IN RECIRCULATION SYSTEM ON WATER QUALITY AND BLOOD GLUCOSE OF Ompok hypopthalmus - Gunawan B S; Usman M Tang; Henni Syawal (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
One of the methods used in intensive cultivation on limited land is the use of a recirculation system with a certain type of filter. This study aims to find the best type of inorganic filter in the cultivation of recirculation systems. This research was conducted from May to August 2019. The materials used were selais fish with a length of 6.8-7.8 cm and a weight of 1.07-2.36 g and fish feed in the form of commercial pellets PF 800. 60x40x40 cm and 60 liter water volume. The method used was an experimental method with one-factor completely randomized design (CRD), namely the type of filter and five levels of treatment (filter type), namely dacron, bioball, gravel, charcoal and zeolite. The parameters measured were the quality of the water in the maintenance medium and the blood glucose levels of the fish. The results showed that the use of different types of filters in the recirculation system had an effect on water quality and blood glucose levels in O. hypopthalmus fish. The results of temperature measurements duringthe study showed that the value of the temperature range was not much different in all treatments, namely in the range, pH and dissolved oxygen were not much different between treatments, namely 26.5 - 29.20C, 7-8, and 4.0- 6.5 mg / L. While the lowest levels of NH3, NO3 and NO2 are found in the bioball filter, namely 0.05 mg / L, 0.65 mg / L and 0.33 mg / L. The treatment with the lowest stress level was the bioball filter, indicated by a blood glucose level of 67.25 mg / dL. Based on the results of the study, it can be concluded that the use of bioball filters in the recirculation system for rearing tilapia (O. hypopthalmus) provides the best results in water quality and reduces stress levels of fish.